Conformity Among College Students: The Effect of Gender on Sexually Violent Beliefs - (:unkn) unknown (My University, 2019)
Sexual violence continues to be a global issue that yields startling statistics of victimhood among collegiate populations. This study explores relationships between gender, social influence, conformity, and gender role orientation, in addition to the impact these factors have on perceptions of sexual violence. Undergraduate students (N = 210) evaluated a vignette detailing a case of possible sexual assault after reading about decisions indicating victim blaming made by previous groups of students. The results showed one’s predisposition to conform and endorse traditional gender roles predicted the likelihood to victim blame and endorse rape myths. Additionally, results revealed that the gender of an individual and a majority group influenced propensity to victim blame. Finally, a surprising finding showed that a male in a female majority group who was a low conformist and less traditional became the most likely to victim blame. An implication from these findings is that groups hold significant power to influence individuals’ decisions, which is problematic when groups make inaccurate judgments and incorrect decisions. A gap exists between understanding theoretical concepts and applications of sexual violence. Relevant limitations and future directions that require further exploration are discussed so that effective preventative efforts can be implemented on college campuses.
Keywords: conformity; gender; majority influence; sexual violence; social influence; victim blame